2003
DOI: 10.1192/bjp.182.6.525
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of brain areas implicated in processing inner speech in people with auditory hallucinations

Abstract: In people with schizophrenia who are prone to auditory hallucinations, increasing the demands on the processing of inner speech is associated with attenuated engagement of the brain areas implicated in verbal self-monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 139 publications
(81 citation statements)
references
References 31 publications
6
74
1
Order By: Relevance
“…A relationship between increased FA values of the fronto-occipital and temporolimbic tracts and more severe positive symptoms has been previously observed in nevermedicated patients with schizophrenia 5,10 and in medicated patients with schizophrenia with a history of auditory hallucinations and other positive symptoms. [26][27][28] Overall, these findings suggest that the observed pattern of structural WM changes in patients with schizophrenia is already present before treatment initiation and is associated with the occurrence of positive clinical manifestations. It is worth noting that MD and FA changes may be secondary to modifications of diffusion either parallel (axial diffusivity) or perpendicular (radial diffusivity) to the principal direction of the tensor.…”
Section: Wm Findingsmentioning
confidence: 72%
“…A relationship between increased FA values of the fronto-occipital and temporolimbic tracts and more severe positive symptoms has been previously observed in nevermedicated patients with schizophrenia 5,10 and in medicated patients with schizophrenia with a history of auditory hallucinations and other positive symptoms. [26][27][28] Overall, these findings suggest that the observed pattern of structural WM changes in patients with schizophrenia is already present before treatment initiation and is associated with the occurrence of positive clinical manifestations. It is worth noting that MD and FA changes may be secondary to modifications of diffusion either parallel (axial diffusivity) or perpendicular (radial diffusivity) to the principal direction of the tensor.…”
Section: Wm Findingsmentioning
confidence: 72%
“…Again, there is a remarkable correspondence with findings in the literature. Several papers have reported abnormalities in subsets of these regions using a variety of techniques (Gaser et al, 2004;Lennox et al, 1999;Shergill et al, 2003;Sibersweig et al, 1995;Stephane et al, 2001;Weiss & Heckers, 1999). This includes a report from our laboratory showing that volumes of the left middle temporal gyrus were correlated with levels of auditory hallucinations (Onitsuka et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that a distributed network of cortical and subcortical areas may mediate auditory hallucinations. The notion that auditory hallucinations might be "inner speech" (thinking in words) was very recently taken further by this same group (46). Previous studies have shown that individuals with schizophrenia who were prone to auditory hallucinations demonstrated attenuated activation of brain areas during the monitoring of inner speech.…”
Section: The Neural Correlates Of Symptomsmentioning
confidence: 96%